2021
DOI: 10.1002/tcr.202100111
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalysed Nitroalkyne Cycloisomerization – Synthetic Utility

Abstract: Dedicated to Professor Christian Bruneau for his outstanding contribution to catalysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Notably, indolone-N-oxides, also known as isatogens, hold substantial importance in medicinal chemistry and serve as intermediates in the synthesis of natural alkaloids and bioactive compounds (Nepveu et al, 2010). The literature contains a wide array of techniques for synthesizing isatogens, encompassing both metal-free and metal-catalyzed routes Dhote, Halnor et al, 2021). These methods have been rigorously explored and well documented, underscoring the adaptability and importance of isatogens in the realms of organic synthesis and medicinal chemistry.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Notably, indolone-N-oxides, also known as isatogens, hold substantial importance in medicinal chemistry and serve as intermediates in the synthesis of natural alkaloids and bioactive compounds (Nepveu et al, 2010). The literature contains a wide array of techniques for synthesizing isatogens, encompassing both metal-free and metal-catalyzed routes Dhote, Halnor et al, 2021). These methods have been rigorously explored and well documented, underscoring the adaptability and importance of isatogens in the realms of organic synthesis and medicinal chemistry.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Compared with conventional step-by-step synthetic procedures, one-pot cascade reactions are more advantageous in terms of reaction efficiency, atom economy, and operation simplicity . In this aspect, o -alkynylnitrobenzene has been employed as an effective component in a number of one-pot cascade reactions leading to the formation of various fused N -heterocycles. , For examples, Ramana et al have reported a one-pot Au­[III]/Lewis acid cocatalyzed cycloisomerization of nitroalkyne followed by [3 + 3] cycloaddition with donor–acceptor cyclopropane to afford structurally interesting tricyclic pseudoindoxyl scaffold (Scheme a) . Song et al disclosed the construction of C2-tetrasubstituted indolin-3-ones through copper-catalyzed radical difluoroalkylation and redox annulation of nitroalkynes with bromodifluoroacetate (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
“…1 Consequently, substantial synthetic efforts have been devoted to construct these important molecules. 2−4 These methods could be divided into three main strategies: (1) oxidative dearomatization of indoles, 2 (2) cyclization of preprepared substrates, 3 and (3) nucleophilic additions to 3H-indol-3-ones 4 or indolone-N-oxides. 5 Indolone-N-oxides (also known as isatogens) have important applications in medicinal chemistry, and they can also be used as intermediates to synthesize natural alkaloids or bioactive molecules.…”
mentioning
confidence: 99%